(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2015)
Growing recognition of significance and the impact that commitment to business ethics has on corporate performance has attracted the interest of scientific and business researchers alike. At the same time, various stakeholders including boards, senior and corporate managers, employees, customers, suppliers, investors, governments and communities have been interested in the correlation between corporate performance in non-financial terms and its commitment to business ethics which has significantly increased its importance as well as its dominant impact in business. Research of the correlation of business ethics and business performance is widely conducted in the developed countries, yet it is still rare in Western Balkans countries, including Croatia, which gave rise to the need to conduct a survey on this topic. The paper comprises preliminary research which examines critical factors that present commitment to business ethics and their influence to non-financial performance indicators of the corporations. The paper also explores why and how the commitment to business ethics can contribute to the creation of corporate values that are eventually reflected in non-financial terms. The paper intends to give executives practical hands-on advice about the benefits of commitment to business ethics in a highly dynamic business environment today. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.